Eletromiografia de superfície em músculos inspiratórios de indivíduos adultos e idosos: revisão sistemática - Reis, Ivanize Mariana Masselli dos (2015)
Introduction: Electromyography (EMG) contributes to the evaluation of disorders and pulmonary changes, since impairments in the respiratory muscles function are associated to the development of diseases. There are wide variety of methods and protocols applied to collect and analyze EMG obtained from respiratory muscles, demonstrating the absence of padronization. Objective: To identify the most commonly procedures applied to record surface EMG (sEMG) of inspiratory muscles in adults and elderly individuals, through a systematic review. Method: Studies published from January 1995 until March 2014 were searched through the keywords (breathing OR respiratory OR inspiratory) AND (electromyography OR EMG) AND (muscle activity OR muscular activity OR muscle activation OR muscular activation OR evaluation OR assessment OR effect) in the following electronic databases: Web of Science, PubMed, LILACS, EBSCO and Embase. Only studies evaluating sEMG in inspiratory muscles were included. Results: We identified 5410 titles and 64 studies, published in English, were included. A great variability of methods applied both record and process/analyze data were found. In general, the description presented by the studies is poor. Conclusion: The most commonly procedures applied were identified and the results obtained did not allow the synthesis of practical/clinical evidences which allow provide immediate recommendations for standardization of the methods to apply sEMG in inspiratory muscles. Thus, methodological studies with objective comparisons are fundamental to the advancement toward standardization.